Practice of Settling Joint Property: A Review Based on The Islamic Law Compilation - Sanjaya, Andra; Muhibbussabry, Muhibbussabry (Batulis Civil Law Review, 2025)
Introduction: Joint property is property obtained during marriage and is an important object in divorce settlement. In practice, joint property settlement is often carried out amicably without going through the courts.Purposes of the Research: This study aims to determine the practice of post-divorce joint property settlement in Padang Cermin Village, Selesai District, Langkat Regency, and to review its compliance with the provisions contained in the Compilation of Islamic Law (KHI).Methods of the Research: This study uses a qualitative approach with a case study method, through interviews, observations, and documentation from related parties, such as former husband and wife, community leaders, and village officials.Results Main Findings of the Research: The results of the study show that joint property settlement in the village is mostly resolved through deliberation by involving family or traditional leaders. However, not all of these processes are in accordance with the provisions of the KHI, especially regarding the principles of justice and the rights of each party. Therefore, more intensive socialization and legal education are needed for the community so that joint property settlement can run in accordance with applicable laws and protect the rights of both parties.